2021
DOI: 10.3390/met11111668
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Tool Shape in Electrical Discharge Machining of EN31 Steel Using Machine Learning Techniques

Abstract: In the electrical discharge machining (EDM) process, especially during the machining of hardened steels, changes in tool shape have been identified as one of the major problems. To understand the aforesaid dilemma, an initiative was undertaken through this experimental study. To assess the distortion in tool shape that occurs during the machining of EN31 tool steel, variations in tool shape were examined by monitoring the roundness of the tooltip before and after machining with a coordinate measuring machine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Machine learning techniques (Walia et al 2021) (CA and FA) were used to optimize the EDM process parameters after identifying the optimum input conditions with Taguchi-PCA based analyses. The prime objective was to increase the MRR and to reduce the RCT and TWR.…”
Section: Resultsmentioning
confidence: 99%
“…Machine learning techniques (Walia et al 2021) (CA and FA) were used to optimize the EDM process parameters after identifying the optimum input conditions with Taguchi-PCA based analyses. The prime objective was to increase the MRR and to reduce the RCT and TWR.…”
Section: Resultsmentioning
confidence: 99%
“…Based on that, solutions are made to get better machinability of HcHcr with improved material removal rate (MRR), reduced surface roughness (SR), and tool wear rate (TWR). In the investigation conducted by Walia, A.S, et al 31 a distortion of 5.65–37.8 μm has been observed in the tooltip of an EDM process on EN31 tool steel. Investigations have shown that a set of parameters is current mainly involved in the tool shape change.…”
Section: Introductionmentioning
confidence: 96%
“…Based on that, solutions are made to get better machinability of HcHcr with improved material removal rate (MRR), reduced surface roughness (SR), and tool wear rate (TWR). In the investigation conducted by Walia, A.S, et al 31 Research suggests that the use of an optimized setting may improve MRR in the machining process of Al6061-SiC. Arulkirubakaran, D., et al 34 have done Performance analysis of ECM with the hexagonal shaped electrode on SS AISI304.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, the combined action of thermal erosion followed by vaporization (by micro-EDM) [4] and electro-chemical etching (by micro-ECM) is responsible for the erosion of materials from the workpiece [5]. Due to the hybridization of the process, a higher rate of material removal (MRR) is attained compared to parent machining processes [6].…”
Section: Introductionmentioning
confidence: 99%